Bacillus cereus AR156 Extracellular Polysaccharides Served as a Novel Micro-associated Molecular Pattern to Induced Systemic Immunity to Pst DC3000 in Arabidopsis - Jiang, Chun-Hao; Fan, Zhi-Hang; Xie, Ping; Guo, Jian-Hua (Frontiers in Microbiology, 2016)
The ability of plants to develop an induced systemic response (ISR) in reaction to root colonization by non-pathogenic bacteria depends on interactions between host plants and the colonizing rhizobacterium. However, how the colonization signal is and how systemic resistance to pathogens is developed is still unclear. In this study, we demonstrated that the extracellular polysaccharides (EPS) of B. cereus AR156 could act as novel microbe-associated molecular patterns (MAMPs) and function in the early perception status of the ISR of B. cereus AR156. The results revealed that B. cereus AR156 EPS could induce systemic resistance to Pst DC3000 in Arabidopsis. Cellular defense response markers such as hydrogen peroxide accumulation, callose deposition, and defense-associated enzyme were induced upon challenge inoculation in the leaves primed by EPS. Moreover, the defense-related genes PR1, PR2, and PR5 and mitogen-activated kinases (MAPK) cascade marker gene MPK6 were concurrently expressed in the leaves of EPS-treated plants and led to a higher level of induced protection against Pst DC3000 in Col-0 than that in the jar1 or etr1 mutants. The protection was absent in the NahG transgenic plants and npr1 mutant, suggesting a NPR1-dependent and simultaneous activation of the salicylic acid (SA)- and the MAPK-dependent signaling pathways by B. cereus AR156 EPS. In conclusion, B. cereus AR156 EPS play an important role in MAMP perception during the process of rhizobacteria-triggered ISR. This study is the first to illustrate how AR156 induces systemic resistance to Pst DC3000 in Arabidopsis. It also provides the first explanation of how plants perceive colonization of non-pathogenic bacteria and how rhizobacteria trigger ISR to plant pathogens.